Chromaticity study of La2O3-PVA nanofibres prepared by electrospinning process for UV light down conversion for white light emitting diode. (16th July 2022) - Wahab, H.A.; Hassan, Z.; Ahmed, N.M.
Lanthanum oxide-polyvinyl alcohol (La2 O3 -PVA) nanofibres had been prepared using electrospinning process with four different thicknesses (2.0, 6.0, 13.0 and 59.0 μm) and each sample with the same thickness was investigated with different annealing temperatures (100, 200, 300 and 500°C). The phosphor was used for light down-conversion of UV light (365 nm) for fabrication of white light emitting diode (WLED). The resulting phosphor nanofibres were observed and analysed by X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) and ultraviolet-visible (UV-Vis) spectroscopy. XRD result confirmed that the fabricated phosphor nanofibres are amorphous. The chromaticity coordinates (CIE) and correlated colour temperature (CCT) of the WLED were measured with different thickness and temperature of phosphor nanofibres by using HPC-2 lightsource colorimeter with applied voltage and current of 8.4 V and 0.14 A, respectively. The comparison showed that lanthanum oxide-polyvinyl alcohol (La2 O3 -PVA) phosphor nanofibres exhibited CIE values of 0.3575, 0.4308 and CCT of 4835 K. An optimum colour rendering index (CRI) value of 66.8 was obtained. The annealing temperature and thickness of phosphor were confirmed to be major factors that control the intensity of white light emitted from the sample.